2021
DOI: 10.3390/biomedicines9111574
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 (SIRT3) Pathways in Age-Related Cardiovascular and Neurodegenerative Diseases

Abstract: Age-associated cardiovascular and neurodegenerative diseases lead to high morbidity and mortality around the world. Sirtuins are vital enzymes for metabolic adaptation and provide protective effects against a wide spectrum of pathologies. Among sirtuins, mitochondrial sirtuin 3 (SIRT3) is an essential player in preserving the habitual metabolic profile. SIRT3 activity declines as a result of aging-induced changes in cellular metabolism, leading to increased susceptibility to endothelial dysfunction, hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 274 publications
(340 reference statements)
1
12
0
Order By: Relevance
“…Our results confirm pterostilbene's efficacy potential and demonstrate its ability to activate SIRT3 as well as its mitochondrial deacetylase function. We hypothesize that pterostilbene, through SIRT3 activation, in combination with mitochondrial cofactors could boost antioxidant mechanisms, enhance fatty acids' β-oxidation, regulate mitochondrial protein quality control and adapt the OXPHOS system, as previously reported in the literature (van de Ven et al, 2017;Silaghi et al, 2021). In general, pterostilbene improves mitochondrial homeostasis and thus palliates the negative impact of mitochondrial mutations.…”
Section: Discussionsupporting
confidence: 61%
“…Our results confirm pterostilbene's efficacy potential and demonstrate its ability to activate SIRT3 as well as its mitochondrial deacetylase function. We hypothesize that pterostilbene, through SIRT3 activation, in combination with mitochondrial cofactors could boost antioxidant mechanisms, enhance fatty acids' β-oxidation, regulate mitochondrial protein quality control and adapt the OXPHOS system, as previously reported in the literature (van de Ven et al, 2017;Silaghi et al, 2021). In general, pterostilbene improves mitochondrial homeostasis and thus palliates the negative impact of mitochondrial mutations.…”
Section: Discussionsupporting
confidence: 61%
“…Recent study reported that LARP7 can ameliorate cellular senescence and aging through enhancing the activity of SIRT1 ( Yan et al, 2021 ). The increase of the expression or activity of SIRT3 can extend the life span of human ( Silaghi et al, 2021 ; Rose et al, 2003 ). Recently, it was found that reduced SIRT3 abundance in mice can exacerbate age-related periodontal disease ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like SIRT1, the declined activity of SIRT3 associated with aging is associated with endothelial dysfunction, hypertension, and heart failure (48). Emerging evidence demonstrated that the stimulated SIRT3 activity could ameliorate cell death, fibrosis, and the inflammatory response of cardiomyocytes under the hypertrophic stimulus, thus improving health and lifespan (49)(50)(51). Besides, silencing SIRT3 may sensitize overload-induced heart failure by worsening cardiomyocyte glucose utilization (52), whereas the impaired SIRT3-mediated endothelium cell metabolism could even result in cardiac diastolic dysfunction (53).…”
Section: Histone Acetylation and Deacetylationmentioning
confidence: 99%